Ethno-Tribal Alienation, Anti-Bullet Charms, and other Factors in the Resurgence of Militancy in the Niger Delta Region of Nigeria - F. A. Ojong; G. E. Odika; J. O. Emeka; D. C. Enamhe; A. M. Ogaboh Agba; A. I. Akintola; V. O. Ogunsola (PT ARRUS Intelektual Indonesia, 2023)
The resurgence of militant groups and the prevailing insecurity situation in the Niger Delta region is the concern of this study. The incessant bombing and vandalisation of oil installation, kidnapping, robbery, etc, has crippled socio-economic activities in the region and Nigeria at large. Although, there exists reports and studies on insecurity in the Niger Delta region, none has provided complete empirical and quantitative account on the effects of ethno-tribal alienation, proliferation of small arms, anti-bullet charms, and amnesty policy inconsistency on the re-emergence of militancy in the Niger Delta region. This knowledge gap justified the relevance of this study. Thus, this study is design to establish the connects between proliferation of small arms, anti-bullet charms, ethno-tribal alienation, amnesty policy inconsistency, insecurity of local chiefs, and the resurgence of militant groups. Findings revealed that Ethno-tribal alienation, proliferation of arms, anti-bullet charms, amnesty policy inconsistency, and insincerity of local chiefs are among the key factors responsible for re-emergence of militancy in the Niger Delta region of Nigeria. Participants noted that they are aware of the potential for repressive and harsh military action as a result of their actions, thus, the study recommended among others that authorities take a more inclusive approach in dealing with the crisis